PENGARUH METODE EKSPERIMEN PADA MATERI WUJUD ZAT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD NEGERI 130 PEKANBARU - Agustina Sitorus, Marsaulina; Adi Putra, M. Jaya; Kartika Sari , Intan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the experimental method on the topic of states of matter on the critical thinking skills of fourth-grade students at SD Negeri 130 Pekanbaru. It was motivated by the fact that many students faced difficulties in distinguishing between solid, liquid, and gas states, as well as their changes, which was caused by conventional learning methods, low literacy levels, and limited facilities and infrastructure. This study employed a quantitative approach with a Nonequivalent Control Group Design. The research subjects consisted of 30 students from class IVA (experimental group) and 30 students from class IVC (control group). Data collection techniques included observation, tests, and documentation, while data analysis was performed using normality tests, homogeneity tests, and Independent Samples T-Test via SPSS version 27. The results indicated a significant increase in the students' average pretest score, which was 46.40 (minimum score of 20 and maximum of 80). After receiving the treatment using the experimental method, the average posttest score increased to 58.93 (minimum score of 20 and maximum of 88), showing a mean improvement of 12.53. Based on the observation of student activities, the most prominent critical thinking skills indicators were basic support and inferences. The Independent Samples T-Test yielded a tvalue of 2,781 with a significance value of 0,007 < 0.05. Consequently, it can be concluded that there is a significant effect of the experimental method on the topic of states of matter toward the critical thinking skills of fourth-grade students at SD Negeri 130 Pekanbaru.